Assistive Technology Innovation Based on Visual Feedback and Computer Vision to Improve Fine Motor Skills in Children with Cerebral Palsy - Mawaddah, Tarisya (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2025)
Cerebral Palsy (CP) affects fine motor development, causing obstacles in daily activities. Existing assistive technologies are often not interactive or adaptive enough, hindering independent learning in children with CP. Fine motor issues in learning are also related to a lack of engaging exercise methods. This research develops assistive technology based on visual feedback and computer vision as an innovative solution to improve fine motor skills in children with CP. This technology utilizes motion sensors for real-time visual feedback, helping children understand and correct movements effectively. The Research and Development (R&D) method was employed, focusing on needs analysis, design, and prototype development using the ADDIE model. Validation results demonstrated the system's feasibility and effectiveness. Subject matter experts scored an average of 3.75, media experts 3.5, and education practitioners 3.67. Trials at SLB ACD Pertiwi Mojokerto showed increased motivation and engagement among children during exercises. This technology is expected to become an effective solution for motor and coordination exercises at school and at home, motivating children with CP to practice and develop their motor skills.